An Analysis of Nyaya Darshana with Special Emphasis on Realism - Pokhrel, Aupson (Nepal Journal of Multidisciplinary Research, 2023)
Nyaya School of Philosophy is distinctly recognized as one of the Six Astika Schools of Hindu Philosophy. Unlike Other Schools, Nyaya is peculiarly known to have proposed five components of Syllogism derived from Inferential Reasoning, both Inductive and Deductive. This treatise aims at clarifying The Nyaya Syllogisms, and successfully arguing for its Logical Realism. Logical Realism, in simple terms, refers to logical facts that are Independent of Mind and Language i.e., they are true synthetic a priori no matter the proposition. This Paper shall advocate the logical structure of Nyaya Syllogism which is independent of both mind and language. Also, the Inferential Reasoning that has been instrumentalized by Gautama to propose such Syllogisms shall be discussed to supplement the paper’s Groundwork. This paper has treated Nyaya in regard to its Epistemology and Logic. The reference to Nyaya, as a metaphysical or Ethical Doctrine, including the ideas of Causation, Fallacies, Truth, and Moksha has, for the most part, been sidelined. The Arguments have been drawn from the Original Works of Gautama called “The Nyaya Sutras” as well as Secondary Works which have further illuminated the works of Gautama. Hence, this Paper shall act as an advancement and supplement to the Nyaya Syllogism. It shall also shed light on the Contributions of Nyaya Syllogism in Syllogistic Logic.